1988
DOI: 10.3168/jds.s0022-0302(88)79563-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Cation-Anion Balance on Milk, Blood, Urine, and Rumen Fluid in Lactating Dairy Cattle

Abstract: Twelve lactating Holstein cows were blocked according to age and milk production into groups of three cows and assigned to three 4 x 4 Latin squares in a split-plot design with subtreatments. Treatments on each square were four diets formulated to provide -10, 0, +10, or +20 meq/Na + K) -Cl/100 g diet DM. The four balances were achieved on squares 1, 2, and 3 by manipulating Na, K, and Cl, respectively. Actual milk yield was 8.6% higher on +20 than -10 averaged across the three squares. Blood pH and bicarbonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
90
7
13

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(169 citation statements)
references
References 12 publications
38
90
7
13
Order By: Relevance
“…As amostras de sangue foram mantidas em refrigeração até a análise, realizada em período máximo de duas horas após a coleta. A urina foi coletada conforme Valadares et al (1997) e analisada para pH, Ca, P, Mg, Na, K, Cl e Creatinina.…”
Section: Methodsunclassified
“…As amostras de sangue foram mantidas em refrigeração até a análise, realizada em período máximo de duas horas após a coleta. A urina foi coletada conforme Valadares et al (1997) e analisada para pH, Ca, P, Mg, Na, K, Cl e Creatinina.…”
Section: Methodsunclassified
“…In contrast, there was a time effect on feed intake, which corresponds with increasing level of anionic salt supplementation. Anionic salts are considered unpalatable (Oetzel et al 1991), and have been shown to depress feed intake in dairy cattle (Tucker et al 1988(Tucker et al , 1992Gaynor et al 1989). The depression in intake appears to be related to alteration of the normal acid-base balance of the animal (Block 1984;Leclerc and Block 1989;Horst et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Block (1984) Tucker et al (1988) in that blood pH and HC03-were lowered by supplementation of dietary chloride and sulfur. Further, urinary hydrogen concentration was lowered by reducing DCAB with either chloride or sulfur.…”
Section: Dairy Cattlementioning
confidence: 99%
“…The effect of DCAB on calcium excretion in the urine is shown in Table V (Topliff et al, 1989;Wall et al, 1992;and Baker et al, 1993), dairy cattle (Tucker et al, 1988) and rabbits (Thacker, 1959) .…”
Section: Urinary Calcium Excretionmentioning
confidence: 99%
See 1 more Smart Citation